Poemat o założeniu Uniwersytetu Poznańskiego - Kotłowska, Anna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The aim of the present paper is to discuss and translate in Polish the poem of Bonawentura Graszyński, written in 1919; with some remarks on author’s interests in Byzantine studies.

The poem about foundation of Adam Mickiewicz University in Poznań was composed in Classical Greek by Bonawentura Czesław Graszyński (1859–1922) in 1919. Graszyński, polish lecturer of classical languages, had also composed few dramas concerning Byzantine realities. The Poem contains ten elegiac distiches with appeal to the Muses for gracing University, which had been recently founded. This article presents Graszyński’s reception of Byzantium and its legacy with a text and translation of his poem.
The poem about foundation of Adam Mickiewicz University in Poznań
Keywords: Adam Mickiewicz University; Bonawentura Graszyński; Modern poetry in Classical Greek